Species of the genus Galathea Fabricius, 1793 (Crustacea, Decapoda, Galatheidae) from the Indian and Pacific Oceans, with descriptions of 92 new species - Macpherson, Enrique; Robainas-Barcia, Aymee (Zootaxa, 2015)
The genus Galathea is one of the most speciose and unwieldy groups in the family Galatheidae. The examination of more than 9000 specimens of 144 species collected in the Indian and Pacific Oceans using morphological and molecular characters, has revealed the existence of 92 new species. The specimens examined during this study were obtained by various French expeditions supplemented by other collections from various sources, and including the type specimens of some previously described species. Most of the new species are distinguished by subtle but constant morphological differences, which are in agreement with molecular divergences of the mitochondrial markers COI and/or 16S rRNA. Here, we describe and illustrate the new species and redescribe some previously described species for which earlier accounts are not sufficiently detailed for modern standards. Furthermore we include a dichotomous identification key to all species in the genus from the Indian and Pacific Oceans.